THE INFLUENCE OF CHILDREN’S PLAYROOM INTERIOR ASPECT IN REGARD TO PARENTAL SAFETY PERCEPTION. CASE STUDY: CHILDREN’S PLAYROOM AT 23 PASKAL BANDUNG, INDONESIA - Rizka Rachmawati; Imtihan Hanom; Santi Salayanti (Malaysian Journal of Public Health Medicine, 2020)
Children’s playrooms in public spaces need to consider the safety of their interior elements. Previous studies also discussed about things that need to be taken into account to assure the children’s safety while playing. However, some parents join their children playing in public spaces due to the cautiousness of playground safety level. This study was conducted to understand how far the interior aspects of children’s playgrounds can affect parents’ safety perception to let their children play by themselves in public spaces, for example, the children’s playroom in 23 Paskal Bandung, West Java, Indonesia. The result shows that sufficient light, interior finishes, and noise or sound intensity in the children’s playground at 23 Paskal Bandung, Indonesia can make parents feel safe to let their children spend time there.